(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Salt deposits in the regions of Uzbekistan and Kazakhstan were discovered in 1943-48 by the first Uzbek chemists S. It was studied by a scientific expedition led by Muqimov (1899-1956). The hydrochemical composition of mineral, saline solutions, the formation laws of saline layers of salt water bodies of "Dengizkul" (Bukhara)," Tuzkon "(Jizzakh)," Shurkon "(Fergana)," Khojakon " (Surkhandarya) were determined. It was shown that these basins are rich in valuable sodium sulfate, as well as potassium, magnesium and bromine salts, in addition to sodium chloride in the salt layers, they contain minerals in the form of astraxonite and eleolite, which contain magnesium and sodium. Experimentally, the practical use of salt mines, saline solutions, and slurry at the bottom of bodies of water were recommended for treatment at local hospitals. Salt baths are a procedure that has a number of beneficial effects on the body, among which: activation of blood circulation, acceleration of metabolic processes, restoration of the body’s protective forces, stimulation of regeneration processes, removal of excess fluid, toxins and other toxic substances from the body and effective result in skin diseases eczema, psoriasis as well as pathologies and injuries of sore muscles and joints, with bruises and cracks, saturation of the body with valuable substances, normalization of the nervous system, restoration action and calming effect.